2020
DOI: 10.1007/s10482-020-01437-y
|View full text |Cite
|
Sign up to set email alerts
|

Thalassoglobus polymorphus sp. nov., a novel Planctomycete isolated close to a public beach of Mallorca Island

Abstract: Access to axenic cultures is crucial to extend the knowledge of the biology, lifestyle or metabolic capabilities of bacteria from different phyla. The phylum Planctomycetes is an excellent example since its members display an unusual cell biology and complex lifestyles. As a contribution to the current collection of axenic planctomycete cultures, here we describe strain Mal48 T isolated from phytoplankton material sampled at the coast of S'Arenal close to Palma de Mallorca (Spain). The isolated strain shows op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The first report of the isolation of a planctomycete in axenic cultures is due to the work of James T. Staley (Staley, 1973). During the last decade, several members of Planctomycetes were isolated in pure culture and described as representing new genera, namely Schlesneria (Kulichevskaya et al, 2007b), Singulisphaera (Kulichevskaya et al, 2008;Kulichevskaya et al, 2012a), Zavarzinella (Kulichevskaya et al, 2009), Aquisphaera (Bondoso et al, 2011), Telmatocola (Kulichevskaya et al, 2012b), Paludisphaera (Kulichevskaya et al, 2016;Kaushik et al, 2020), Roseimaritima (Bondoso et al, 2015;Kumar et al, 2020b), Rubripirellula (Bondoso et al, 2015;Kallscheuer et al, 2019b), Fimbriiglobus (Kulichevskaya et al, 2017a), Tundrisphaera (Kulichevskaya et al, 2017b), Mariniblastus (Lage et al, 2017), Caulifigura (Kallscheuer et al, 2020a), Tuwongella (Seeger et al, 2017), Crateriforma (Peeters et al, 2020c), Fuerstia (Kohn et al, 2016;Kohn et al, 2019), Novipirellula (Kallscheuer et al, 2019c), Tautonia (Kovaleva et al, 2019;Jogler et al, 2020) Limnoglobus (Kulichevskaya et al, 2020b), Thalassoglobus (Kohn et al, 2020a;Rivas-Marin et al, 2020c), Symmachiella (Salbreiter et al, 2020), Gimesia (Scheuner et al, 2014;Kumar et al, 2020a;Wang et al, 2020), Stieleria (Sandargo et al, 2020;Storesund et al, 2020;Surup et al, 2020), Aureliella (Kallscheuer et al, 2020b), Maioricimonas (Rivas-Marin et al, 20...…”
Section: Cultured Planctomycetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first report of the isolation of a planctomycete in axenic cultures is due to the work of James T. Staley (Staley, 1973). During the last decade, several members of Planctomycetes were isolated in pure culture and described as representing new genera, namely Schlesneria (Kulichevskaya et al, 2007b), Singulisphaera (Kulichevskaya et al, 2008;Kulichevskaya et al, 2012a), Zavarzinella (Kulichevskaya et al, 2009), Aquisphaera (Bondoso et al, 2011), Telmatocola (Kulichevskaya et al, 2012b), Paludisphaera (Kulichevskaya et al, 2016;Kaushik et al, 2020), Roseimaritima (Bondoso et al, 2015;Kumar et al, 2020b), Rubripirellula (Bondoso et al, 2015;Kallscheuer et al, 2019b), Fimbriiglobus (Kulichevskaya et al, 2017a), Tundrisphaera (Kulichevskaya et al, 2017b), Mariniblastus (Lage et al, 2017), Caulifigura (Kallscheuer et al, 2020a), Tuwongella (Seeger et al, 2017), Crateriforma (Peeters et al, 2020c), Fuerstia (Kohn et al, 2016;Kohn et al, 2019), Novipirellula (Kallscheuer et al, 2019c), Tautonia (Kovaleva et al, 2019;Jogler et al, 2020) Limnoglobus (Kulichevskaya et al, 2020b), Thalassoglobus (Kohn et al, 2020a;Rivas-Marin et al, 2020c), Symmachiella (Salbreiter et al, 2020), Gimesia (Scheuner et al, 2014;Kumar et al, 2020a;Wang et al, 2020), Stieleria (Sandargo et al, 2020;Storesund et al, 2020;Surup et al, 2020), Aureliella (Kallscheuer et al, 2020b), Maioricimonas (Rivas-Marin et al, 20...…”
Section: Cultured Planctomycetesmentioning
confidence: 99%
“…They require a specific culture medium and long incubation times (Franzmann and Skerman, 1984;Lee et al, 2009;Wiegand et al, 2020). Accordingly, most knowledge regarding the environmental and host-associated microbiota niches of Planctomycetes organisms is derived from DNA-based studies including PCR-sequencing-based analyses and metagenomics studies (Cayrou et al, 2013;Bondoso et al, 2014;Drancourt et al, 2014;Delmont et al, 2018;Dedysh et al, 2020a), although there have been considerable advances to date, that have made it possible to isolate many species of this phylum from host-associated Planctomycetes from environmental habitats (Dedysh et al, 2020b;Jogler et al, 2020;Kallscheuer et al, 2020b;Kaushik et al, 2020;Kohn et al, 2020b;Kulichevskaya et al, 2020a;Kulichevskaya et al, 2020b;Rivas-Marin et al, 2020b;Rivas-Marin et al, 2020c;Salbreiter et al, 2020;Sandargo et al, 2020;Schubert et al, 2020;Wang et al, 2020;Wiegand et al, 2020). Hence, enormous work remains to be done to improve their culture and their isolation, in view of the enormity of 16S rRNA genes sequenced deposited in GenBank but have never yet been isolated in pure culture (uncultured Planctomycetes) up to the present day (see review Wiegand et al, 2018 for more details) because, the true knowledge of bacterial taxonomy, physiology, and pathogenicity has long time based only on the isolation of the strain in pure culture and presents several challenges for clinical microbiologists.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the first two described planctomycetal isolates from macroalgae belong to the class Phycisphaerae [ 24 , 25 , 26 ]. In recent years, single-cell genomes [ 27 ] and axenic cultures from macroalgae were also obtained for the families Pirellulaceae [ 28 , 29 , 30 , 31 ], Lacipirellulaceae [ 32 ], Planctomycetaceae [ 33 , 34 , 35 ], and Isosphaeraceae [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of 131 genomes (Table S1 ) uncovered that 91 genomes encode at least one type III PKS. A single strain, Thalassoroseus polymorphus Mal48 T , carries two type III PKS genes (Rivas-Marin et al 2020 ), whereas even three type III PKS genes were found in two strains, Lacipirellula parvula PX69 T and Lacipirellula limnantheis I41 T (Dedysh et al 2020 ; Kallscheuer et al 2021 ). With the presence of type III PKS genes in 70% of the known species (91 out of 131 planctomycetal genomes), these genes are found in a majority of the phylum, but are not conserved in all species.…”
Section: Resultsmentioning
confidence: 99%